Mosquito and Virus Surveillance as a Predictor of Human Ross River Virus Infection in South-West Western Australia: How Useful Is It? - Walker, Liz J. (Am J Trop Med Hyg, 2018)
Mosquito and virus surveillance systems are widely used in Western Australia (WA) to support public health efforts to reduce mosquito-borne disease. However, these programs are costly to maintain on a long-term basis. Therefore, we aimed to assess the validity of mosquito numbers and Ross River virus (RRV) isolates from surveillance trap sites as predictors of human RRV cases in south-west WA between 2003 and 2014. Using negative binomial regression modeling, mosquito surveillance was found to be a useful tool for predicting human RRV cases. In eight of the nine traps, when adjusted for season, there was an increased risk of RRV cases associated with elevated mosquito numbers detected 1 month before the onset of human cases for at least one quartile compared with the reference group. The most predictive urban trap sites were located near saltmarsh mosquito habitat, bushland that could sustain macropods and densely populated residential suburbs. This convergence of environments could allow enzootic transmission of RRV to spillover and infect the human population. Close proximity of urban trap sites to each other suggested these sites could be reduced. Ross River virus isolates were infrequent at some trap sites, so ceasing RRV isolation from mosquitoes at these sites or where isolates were not predictive of human cases could be considered. In future, trap sites could be reduced for routine surveillance, allowing other environments to be monitored to broaden the understanding of RRV ecology in the region. A more cost-effective and efficient surveillance program may result from these modifications.